2004
DOI: 10.1016/j.femsec.2004.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of formation waters from the deep repository of liquid radioactive wastes Severnyi

Abstract: The presence, diversity, and geochemical activity of microorganisms in the Severnyi repository of liquid radioactive wastes were studied. Cultivable anaerobic denitrifiers, fermenters, sulfate-reducers, and methanogens were found in water samples from a depth of 162-405 m below sea level. Subsurface microorganisms produced methane from [2-(14)C]acetate and [(14)C]CO(2), formed hydrogen sulfide from Na(2) (35)SO(4), and reduced nitrate to dinitrogen in medium with acetate. The cell numbers of all studied groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Not surprisingly, the contamination often resulted in an apparent enrichment for microbes that could degrade or otherwise utilize the contaminants (e.g., Lowe et al 2002;de Lipthay et al 2003), or microbes that were comparatively resistant to highly toxic contaminants (e.g., Fredrickson et al 2004;Reardon et al 2004). Contamination has also been associated with increased cultivatability (de Lipthay et al 2003) or metabolic activity (Nazina et al 2004) of microbes within the contaminant plume. In contrast, some types of contaminants appeared to have little or no affect on subsurface • Viable bacterial numbers low (∼10 4 CFU g 2 ) but cultures recovered from 11 of 16 samples, including most radioactive (e.g., >10 µCi of 137 Cs/g) • Isolates/clones from contaminated sediments dominated by Gram-positive species; Arthrobacter most common but other high-G+C phyla present • Two isolates related to Deinococcus radiodurans able to survive doses of ionizing radiation up to 20 kGy; many Gram-positive isolates resistant to lower levels of gamma radiation Vadose-zone, nutrient-poor glacial melt water sand; influence of petroleum hydrocarbon vapors on microbial community structure…”
Section: Microbial Diversity and Community Structurementioning
confidence: 99%
“…Not surprisingly, the contamination often resulted in an apparent enrichment for microbes that could degrade or otherwise utilize the contaminants (e.g., Lowe et al 2002;de Lipthay et al 2003), or microbes that were comparatively resistant to highly toxic contaminants (e.g., Fredrickson et al 2004;Reardon et al 2004). Contamination has also been associated with increased cultivatability (de Lipthay et al 2003) or metabolic activity (Nazina et al 2004) of microbes within the contaminant plume. In contrast, some types of contaminants appeared to have little or no affect on subsurface • Viable bacterial numbers low (∼10 4 CFU g 2 ) but cultures recovered from 11 of 16 samples, including most radioactive (e.g., >10 µCi of 137 Cs/g) • Isolates/clones from contaminated sediments dominated by Gram-positive species; Arthrobacter most common but other high-G+C phyla present • Two isolates related to Deinococcus radiodurans able to survive doses of ionizing radiation up to 20 kGy; many Gram-positive isolates resistant to lower levels of gamma radiation Vadose-zone, nutrient-poor glacial melt water sand; influence of petroleum hydrocarbon vapors on microbial community structure…”
Section: Microbial Diversity and Community Structurementioning
confidence: 99%
“…In deep levels in Hungary (198-229 m), which are to be used for waste disposal [14], the population of aerobic microorganisms does not exceed 10 2 and anaerobic organisms 10 4 per 1 cm 3 . Close values were also found in waters in the deep liquid-wastes repository at the Severnyi site [6,7]. Investigations [6,7,12,13]have shown that microorganisms living in underground formations are capable of forming gasesmethane, carbon dioxide, hydrogen, hydrogen sulfide, nitrogen, and others -from possible macrocomponents of the liquid wastes.…”
mentioning
confidence: 82%
“…Constant geological and hydrogeological monitoring (measurement of the temperature, pressure, piezolevels, and so forth) in injection and observation wells is performed on these sites, and the composition of the gases released from the injection wells is also analyzed [5]. In recent years, serious attention has been devoted to investigating the microflora in underground levels used for burying liquid wastes [6,7]. The main objects of investigation were samples of formation water from observational wells in the second level (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations